"The Right to Education Act, 2009: Bridging Socio-Legal Gaps in Policy Implementation Through Administrative Reform At Ranchi In Jharkhand” (Journal of Informatics Education and Research, 2025)
The Right of Children to Free and Compulsory Education Act, 2009 (RTE Act) was a major turning point in India's dedication to universal elementary education. This research critically analyzes the socio-legal gaps that still exist in the enforcement of the RTE Act with a concentrated case study of Ranchi, Jharkhand. In spite of the Act's assurance, deep-seated problems—varying from poor infrastructure and teacher shortages to low levels of public awareness and bureaucratic lethargy—have prevented its effective implementation. The paper examines how local-level administrative reforms can be a game-changer in filling these gaps. Through field studies, policy analysis, and interviews with stakeholders, the research brings out institutional weaknesses and innovative local efforts in Ranchi. It contends that simple legislative intention alone is not enough without strong administrative mechanisms, local community engagement, and accountability systems. The findings indicate that empowering school management committees, strengthening grievance redressal mechanisms, and facilitating interagency coordination with civil society organizations are central to enhancing RTE implementation. The article concludes that although the RTE Act provides a robust legal framework, its success depends finally on adaptive, decentralized governance and long-term political will at the grassroots level.